PKM PENGENALAN SENAM 6 LANGKAH CUCI TANGAN DAN SENAM IRAMA PADA SISWA KELAS 5 DAN 6 DI SDN 011 BUKIT KRATAI RUMBIO JAYA - Zurrahmi Z.R; Sri Hardianti; Fitria Meiriza Syahasti (COVIT (Community Service of Health), 2021)
Washing hands is one of the behaviors of a clean and healthy life. Correct hand washing behavior using 6 steps and soap. Correct hand washing behavior can reduce diarrheal disease and ARI. Children often do not wash their hands properly, most do not use soap and only wet with water. The method used is a 6-step hand washing exercise and rhythmic gymnastics about proper hand washing using the baby shark dance song. Solving problems for children who are bored and lazy to wash their hands, an introduction to how to wash their hands is good and right by using the baby shark song, so that children can remember the steps to wash their hands while singing. This activity was carried out in 2 stages, the first stage was to explain the steps for washing hands properly and correctly. Seven steps of hand washing Washing hands with soap and running water to clean the fingers, palms, backs of hands and wrists from all dirt, germs and bacteria that cause disease. The second stage is doing good and correct hand washing steps accompanied by a baby shark song. The results of this activity increase students' knowledge of 6 steps of hand washing gymnastics, improve hand washing skills properly and correctly. The conclusion is that there is an increase in students' knowledge and skills in 6 steps of proper hand washing and using soap in an interesting and fun way using baby shark dance songs.